Development of food-grade bigels based on κ-carrageenan hydrogel and monoglyceride oleogels as carriers for β-carotene: Roles of oleogel fraction. (August 2020) - Zheng, Hongxia; Mao, Like; Cui, Mengnan; Liu, Jinfang; Gao, Yanxiang
Abstract: Bigels based on κ-carrageenan hydrogel and monoglyceride oleogels were developed as carriers for lipophilic bioactives. Bigels were prepared by mixing the hydrogel and oleogels under temperature control, and the roles of oleogel fraction in the structures of the bigels and the delivery of β-carotene were investigated. Microstructural observation indicated that the structures of bigels changed from oleogel-in-hydrogel type (25, 40, 50%) to bi-continuous type (60%) and to hydrogel-in-oleogel type (75%). Mechanical properties (storage modulus, stiffness, fracture stress) of the bigels were enhanced with higher content of oleogel, and the biggest enhancement was observed when the bigel was transformed into bi-continuous or hydrogel-in-oleogel structures. XRD analysis revealed the crystalline structures of monoglyceride and liquid state of the corn oil, and the highest crystallinity was found in the bigel with 50% oleogel. Thermal stability of the bigels was improved with the increase in oleogel fraction, as monoglyceride tended to melt at higher temperature with higher oleogel content. All the bigels had low swelling ratio except for the sample with 50% oleogel. When bigels were used to encapsulate β-carotene, oleogel fraction also influenced stability and in vitro gastrointestinal release of the bioactive. Both light stability and thermal stability of β-carotene were improved with the increase in oleogel fraction, and about 70% of the original β-carotene could be retained after 8 h of UV-light exposure in the bigel with 75% oleogel. All the bigels had minor release in simulated gastric juice, and the release ratios were greatly increased in the simulated intestinal juice, and higher content of oleogel could promote the release. Graphical abstract: Image 1 Highlights: Bigels based on monoglyceride oleogels and κ-carrageenan hydrogel were developed. The types of bigels were varied by changing oleogel fraction. Higher oleogel fraction enhanced the mechanical properties of the bigels. β-Carotene incorporated in bigels had improved stability with the increase in oleogel content. β-Carotene had higher release in bigels with higher oleogel fraction.